IMPLEMENTASI DEMOKRASI DALAM PERANAN AHLU AL-HALLI WA AL-‘AQDI - Syukur, Iskandar (Universitas Islam Negeri Raden Intan Lampung, 2019)
This paper discusses the implementation of democracy in the role of Ahlu al-Halli Wa al-'Aqdi. It is a representative institution (legislative body) of various elements in society and given some authorities to accommodate and carry out people's aspirations; starting from the matter of electing/appointing state leaders until making laws to regulate other matters related to the interests of the state and the people. In setting a case, the Ahlu al-Halli Wa al-'Aqdi institution, firstly, must be based on the provisions of Allah SWT and His Prophet and, secondly, based on deliberation in line with the provisions of Allah SWT or according to the spirits/values of Islam/Shari'ah. Ahlu al-Halli Wa al-qAqdi's membership consists of people who have great strength both in terms of personality and expertise. However, Muslim scholars differ on the number of members of this institution in the context of electing/appointing state leaders. By discussing the existence of Ahlu al-Halli Wa al-qAqdi as a representative institution, and it always prioritizes the process of deliberation in deciding all cases that become under its authority, then the existence and role of Ahlu al-Halli Wa al-qAqdi institution are parts of the democratic process.Key Words: Demokrasi, Peranan, Ahlu al-Halli Wa al-‘Aqdi